2002
DOI: 10.1111/j.1365-2621.2002.tb11416.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Blanching of Vegetables

Abstract: Three vegetables, spinach, carrot, and bell peppers were blanched conventionally in water and using pulsed microwave at 95 Ϯ Ϯ Ϯ Ϯ Ϯ 2 C. The effect of various parameters like mass of the product, mobility of the product in the microwave field, and physical geometry on the temperature attained was evaluated. The study also included the kinetics of peroxidase inactivation, temperature, and power distribution during microwave blanching. The study highlights the potential application of microwave blanching in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 20 publications
(12 reference statements)
7
65
0
11
Order By: Relevance
“…En relación a la cocción por microondas, los resultados del presente estudio son semejantes con los encontrados por Campbell et al (1958), Tannenbaum (1979), Marrizal et al (1997), Howard et al (1999), Kaur y Kapoor (2001) y Ramesh et al (2002), que observaron que la retención de vitamina C fue mayor en los alimentos cocidos por microondas que en los cocidos a ebullición.…”
Section: Método De Cocciónunclassified
See 2 more Smart Citations
“…En relación a la cocción por microondas, los resultados del presente estudio son semejantes con los encontrados por Campbell et al (1958), Tannenbaum (1979), Marrizal et al (1997), Howard et al (1999), Kaur y Kapoor (2001) y Ramesh et al (2002), que observaron que la retención de vitamina C fue mayor en los alimentos cocidos por microondas que en los cocidos a ebullición.…”
Section: Método De Cocciónunclassified
“…En relación a la cocción por microondas, los resultados del presente estudio son semejantes con los encontrados por Campbell et al (1958), Tannenbaum (1979), Marrizal et al (1997), Howard et al (1999), Kaur y Kapoor (2001) y Ramesh et al (2002), que observaron que la retención de vitamina C fue mayor en los alimentos cocidos por microondas que en los cocidos a ebullición. Gester (1989) afirma que, debido a que la cocción utilizando microondas exige menor tiempo para la preparación del alimento, éste es expuesto al calor por un En relación a la coliflor, se observó una diferencia significativa (p≤0,05) entre las muestras ultracongeladas y en fresco solamente con respecto al color cuando fueron sometidas a ebullición, siendo la coliflor en fresco la preferida.…”
Section: Análisis Sensorialunclassified
See 1 more Smart Citation
“…Microwave heating was primly applied in agriculture, in grain drying and insect control. In addition, it was used for food drying, blanching, pasteurization and cooking (Chen et al, 1971;Lin & Li, 1971;Maurer et al, 1971;Bhartia et al, 1973;Nelson, 1973;Jaynes, 1975;Avisse & Varaquaux, 1977;Nykvist & Decareau, 1976;Sobiech, 1980;Shivhare et al, 1994;Tulasidas et al, 1995;Begum & Brewer, 2001;Hong et al, 2001;Sumnu, 2001;Ramesh et al, 2002;Beaudry et al, 2003;Severini et al, 2004;Williams et al, 2004;Zhang et al, 2004). Frozen materials are usually thawed or tempered before further processing in food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The major reason for this behavior is the existence of isoenzymes with different heat-stability in vegetables (Chilaka et al, 2002). Ramesh et al (2002) reported the results of using pulsed microwave to blanch spinach, carrot, and bell peppers at 95°C, and established the kinetics of POD inactivation. Sheu and Chen (1991) studied blanching vegetable soybeans prior to freezing using lipoxygenase (LIP) and POD (auxiliary index) as indices.…”
Section: Introductionmentioning
confidence: 99%